The Effectiveness of Project-Based Learning on 21st-Century Skills in Elementary Schools: A Literature Review - RINCI SIMBOLON; Saraswati Silalahi (BASICA, 2025)
21st-century skills (4C: Critical thinking, Creativity, Collaboration, Communication) are crucial competencies that must be instilled from an early age, especially at the elementary school level to support the implementation of the Merdeka Curriculum. One of the recommended innovative learning models to equip these skills is Project-Based Learning (PjBL). This study aims to analyze and synthesize the effectiveness of the PjBL model in Natural and Social Sciences (IPAS) and integrative learning clusters in improving the 21st-century skills of elementary school students. The method used is a literature review with a descriptive-analytical qualitative approach. Data collection was conducted through online searches on the Google Scholar database for scientific articles published between 2021 and 2026. Based on strict inclusion and exclusion criteria, 9 main articles were obtained and analyzed using content analysis techniques. The results of the literature review indicate that the PjBL model consistently has a high level of effectiveness (ranging from 45.5% to 50% highly effective) in boosting students' critical thinking skills and creativity, particularly when integrated with the STEAM approach and local wisdom values. Furthermore, the group-based syntax of PjBL significantly builds collaboration skills (mutual cooperation) and communication courage through the presentation phase of solutif products. The main challenges identified include time management limitations and teachers' low understanding of complete project syntax. This study recommends the importance of optimizing teachers' pedagogical competence in designing efficient and contextual projects